Lip Volumination in HOF: A Narrative Literature Review (Research, Society and Development, 2023)
Orofacial harmonization is a dental specialty that precedes the need to expand and associate treatments between intra and extraoral structures, rehabilitating functions and restructuring anatomical units that have undergone changes over time, making it possible to restore confidence and self-esteem to patients across different age groups. The objective of the work is to emphasize the importance of the lip and the harmony of the face, through proportions and lip measurements, considering individuality and society's perception, returning satisfaction to the patient. Data collection took place in the PubMed, LILACS and Scielo databases, indicating the following descriptors in the search field: “Lip”, “Orofacial Harmonization” and “Aesthetics”. For advanced search, correlating terms, Boolean operators and were used. There was no restriction for the type of article to be inserted in the references, as well as a publication date limit of 09 years. The analysis for the selection of the articles was of the qualitative type, integrating any and all research methodology that relates the terms "Lip", "Orofacial Harmonization" and "Aesthetics". The various applications and context of lip volumization within the orofacial harmonization specialty were textually described. It was concluded through the studies presented that there is no standard formula, but a correct evaluation and indication of techniques, and it is up to the professional to adapt them in the face of diversity.